1988
DOI: 10.1136/thx.43.4.342
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis in nurses: is there an association?

Abstract: A retrospective survey of patients with sarcoidosis has revealed a 7 5 times greater number of nurses with the condition than expected. Nurses may be especially susceptible to sarcoidosis.A recent case-control study in the Isle of Man observed an excess of health workers with sarcoidosis' and a companion study found a clustering of cases around a hospital.2 Both studies concluded that sarcoidosis may be a communicable disease. This report provides further evidence of an association between sarcoidosis and hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 3 publications
1
21
0
2
Order By: Relevance
“…Seasonal clusterings of sarcoidosis in the months of June and July [61], time and space clusters [62,63], an increased incidence in health workers [64] and the transmission of sarcoidosis by transplants [65] have been observed and further support the hypothesis of transmissible sarcoid-inducing agents. For example, Borrelia burgdorferi has recently been proposed as a possible cause of sarcoidosis [66,67], although data obtained by the author's group do not support this hypothesis [68].…”
Section: Aetiologysupporting
confidence: 58%
“…Seasonal clusterings of sarcoidosis in the months of June and July [61], time and space clusters [62,63], an increased incidence in health workers [64] and the transmission of sarcoidosis by transplants [65] have been observed and further support the hypothesis of transmissible sarcoid-inducing agents. For example, Borrelia burgdorferi has recently been proposed as a possible cause of sarcoidosis [66,67], although data obtained by the author's group do not support this hypothesis [68].…”
Section: Aetiologysupporting
confidence: 58%
“…Epidemiological data and similarities with other infectious diseases support the hypothesis that sarcoidosis is induced by an infectious organism or its remnants. Seasonal clustering of sarcoidosis in the months of June and July [27], change of prevalence over climate zones [9], time and space clusters [28,29], an increased incidence in health workers [30], an association of environmental exposure with sarcoidosis [31] or specific sarcoidosis phenotypes [32] and the transmission or recurrence of sarcoidosis by or in transplants [33,34] have been observed and support the hypothesis of transmissible animate sarcoidosis-inducing agents. Numerous case series, case reports, and epidemiologic studies demonstrated an association between sarcoidosis with uptake of silica [31], talc [35,36], man-made fibres [37] or other inanimate agents [38,39] by inhalation or ingestion at work place [28,32,[40][41][42], at home [32,43], from the environment [32] or as components of pharmaceutical products [44].…”
Section: Etiologymentioning
confidence: 92%
“…Other authors also suggested that OFG is a descriptive term and the specific cause of these lesions is unknown (Shams et al, 2007). Some authors (Edmondstone & Wilson, 1985 ;Hills et al, 1987 ;Edmondstone, 1988;Bardinas et al, 1989 ;Panayeas et al, 1991 ;Rybicki et al,1997) have reported a familial, (i.e. among people in the same household), seasonal and occupational clustering of sarcoidosis, suggesting a multifactorial origin that includes genetic predisposition, infectious organisms and environmental exposures as probable underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%